Lichen collection in the Herbarium of the University of İstanbul (ISTF) - (:unkn) unknown (My University, 2005)
The unidentified lichen specimens collected about 50 years ago and stored in the herbarium of the Faculty of Science, the University of İstanbul (ISTF) were examined taxonomically and identified. This lichen collection includes 67 species, some of which are rare and interesting for the collection sites. Most of the samples are from İstanbul and its surroundings, but some are from several provinces in Anatolia. © TÜBİTAK.
Keywords: Flora; İstanbul; ISTF; Lichen; Turkey